2012
DOI: 10.1007/s11434-012-5384-8
|View full text |Cite
|
Sign up to set email alerts
|

Os isotopic evidence for a carbonaceous chondritic mantle source for the Nagqu ophiolite from Tibet and its implications

Abstract: Early-crystallizing chromian spinel (Cr-spinel) in the Nagqu ophiolite has high Os and low Re contents, and it is resistant to alteration during serpentinization, weathering and metamorphism. The chemical composition of primitive magma is preserved in Cr-spinel, which makes it suitable for determining the initial Os-isotope composition of the mantle source. This study presents Cr-spinel Os isotopes and zircon U-Pb ages for cumulate dunite and gabbro, respectively, in the same cumulate section of the ophiolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…The ophiolite was tectonically emplaced into the Jurassic Mugagangri Group. Previous studies suggested that the Nagqu ophiolite was formed during the initiation of subduction or in a back-arc setting (Huang et al, 2013;Wang et al, 1985). The Nagqu ophiolite predominantly consists of mantle peridotites that tectonically overlie a cumulate complex.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The ophiolite was tectonically emplaced into the Jurassic Mugagangri Group. Previous studies suggested that the Nagqu ophiolite was formed during the initiation of subduction or in a back-arc setting (Huang et al, 2013;Wang et al, 1985). The Nagqu ophiolite predominantly consists of mantle peridotites that tectonically overlie a cumulate complex.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The Nagqu ophiolite predominantly consists of mantle peridotites that tectonically overlie a cumulate complex. This complex consists of dunites at the base and layered gabbro in the upper part, with interleaved olivine-pyroxenite and pyroxenite horizons (Huang et al, 2013). The mantle section is mainly composed of heavily serpentinized harzburgites and dunites associated with chromitites.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Huang et al [319] show that definite some cha-racteristics of chromites (e.g., 187 Os/ 188 Os) from the Nagqu ophiolite (Tibet) suggest that the mantle source for the dunite is similar to that of the carbonaceous chondrites. Yang et al [320] …”
Section: Relationships Of Pges and Pgms Ore Deposits Formation With Pmentioning
confidence: 99%
“…The Bangong-Nujiang Suture (BNS), one of the major sutures in the Tibetan area (Figure 1a), whose ophiolites are derived mainly from a supra-subduction zone (Zhou, Malpas, Robinson, & Reynolds, 1997;Zhang, 2007;Wang, Aitchison, Lo, & Zeng, 2008;Wang et al, 2016;Xu, Xia, Li, & Zhong, 2010;Shi et al, 2012;Huang et al, 2013;Huang et al, 2017. The Zangbei lakes region within middle segment of the BNS contains many ophiolites (e.g., Dongqiao, Amdo, Jiangtso, Naqu, Lanong, and Darutso; Figures 1c and 2a) and whose origins and tectonic evolution are ambiguous.…”
mentioning
confidence: 99%
“…The Zangbei lakes region within middle segment of the BNS contains many ophiolites (e.g., Dongqiao, Amdo, Jiangtso, Naqu, Lanong, and Darutso; Figures 1c and 2a) and whose origins and tectonic evolution are ambiguous. The vast majority of data on mafic rocks and geochronology suggest that the Zangbei lakes region ophiolitic fragments formed during the Mesozoic (Huang et al, 2013;Li, Wang, Liu, Wang, & Chen, 2015;Liu et al, 2016;Shi et al, 2012; FIGURE 1 (a) Topography, terranes, sutures, and principal structural units of the Tibetan Plateau (Chung et al, 1998;Kapp et al, 2003;Tapponnier et al, 2001;Yin & Harrison, 2000). (b) Generalized geologic map of the middle BNS showing the distribution and isotope ages of the sedimentary strata, ophiolitic fragments, and arc-related rocks along the SQ and NL (Zhu et al, 2016).…”
mentioning
confidence: 99%